2016
DOI: 10.1007/s12178-016-9371-6
|View full text |Cite
|
Sign up to set email alerts
|

Current management of aneurysmal bone cysts

Abstract: Aneurysmal bone cysts (ABCs) are benign bone lesions arising predominantly in the pediatric population that can cause local pain, swelling, and pathologic fracture. Primary lesions, which constitute roughly two thirds of all ABCs, are thought to be neoplastic in nature, with one third of ABCs arising secondary to other tumors. Diagnosis is made with various imaging modalities, which exhibit characteristic features such as Bfluid-fluid levels,^although biopsy is critical, as telangiectatic osteosarcoma cannot b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
259
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 188 publications
(285 citation statements)
references
References 59 publications
1
259
0
7
Order By: Relevance
“…There were five males and four females with a median age of 12.5 (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) years at diagnosis. The median age at the beginning of denosumab treatment was 12.58 (range 5-18) years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were five males and four females with a median age of 12.5 (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) years at diagnosis. The median age at the beginning of denosumab treatment was 12.58 (range 5-18) years.…”
Section: Resultsmentioning
confidence: 99%
“…Complete improvement may generally not be possible with those treatments unless a wide resection has been performed, which may not be feasible in most of the cases because of potential functional and anatomical deficits. The recurrence rate in incomplete resection exceeds 20% . As a result, new and potentially less invasive treatments for ABC are being investigated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they found BRC in only 14% of cases of aneurysmal bone cysts. 13,14 For the common scenario in which aneurysmal bone cysts is difficult to distinguish from TOS or other giant-cell containing lesions, genomic analysis is an invaluable tool. While fine-needle aspiration is less expensive, less invasive, and relatively easy to perform, Creager et al concluded that FNA does not yield findings that are specific enough to diagnose aneurysmal bone cysts.…”
Section: Discussionmentioning
confidence: 99%
“…12 Due to the lack of conclusive evidence on minimally invasive diagnostic techniques, the American Academy of Orthopedic Surgery still designates open biopsy as the standard of care. 13,14 For the common scenario in which aneurysmal bone cysts is difficult to distinguish from TOS or other giant-cell containing lesions, genomic analysis is an invaluable tool. Szuhai FIGURE 4 Metabolic response to denosumab treatment PET/CT in left column showing metabolically active aneurysmal bone cysts of the right maxillary sinus and anterior skull base prior to treatment.…”
Section: Discussionmentioning
confidence: 99%